Living Emotions, Avoiding Emotions: Behavioral Investigation of the Regulation of Socially Driven Emotions - Grecucci, Alessandro; Giorgetta, Cinzia; bonini, nicolao; sanfey, alan g. (Frontiers in Psychology, 2013)
Emotion regulation is very important for psychological well-being. Although it is known that alternative regulation strategies may have different emotional consequences, the effectiveness of such strategies for socially driven emotions remains unclear. In this study we investigated the efficacy of different forms of reappraisal on responses to the selfish and altruistic behavior of others in the Dictator Game. In Experiment 1, subjects mentalized the intentions of the other player in one condition, and took distance from the situation in the other. Emotion ratings were recorded after each offer. Compared with a baseline condition, mentalizing led subjects to experience their emotions as more positive when receiving both selfish and altruistic proposals, whereas distancing decreased the valence when receiving altruistic offers, but did not affect the perception of selfish behaviors. In Experiment 2, subjects played with both computer and human partners while reappraising the meaning of the player’s intentions (in case of a human partner) or the meaning of the situation (in case of a computer partner). Results showed that both contexts were effectively modulated by reappraisal, however a stronger effect was observed when the donor was a human partner as compared to a computer. Taken together, these results demonstrate that socially driven emotions can be successfully modulated by reappraisal strategies that focus on the reinterpretation of others’ intentions.